Features of carbon diffusion during plasma electrolytic carburising of low-carbon steels - Схадрин S. Y.; Кусманов S. A.; Ковризхнйкх T. A.; Белкин P. N. (Materials. Technologies. Design, 2020)
This work is devoted to evaluation of the diffusion coefficient of carbon using the thickness of the martensitic layer after plasma electrolytic carburizing in various electrolytes followed by quenching. The carbon diffusion coefficient was calculated using the solution of the diffusion equation for a semi-infinite body according to the thickness of the martensitic layer which was measured by means of an optical microscope. The effective diffusion coefficients of carbon in the structure of mild steel containing oxide and martensitic layers are determined. The maximum diffusion coefficient at a carburising temperature of 900 °C is 2.3 ? 10–7 cm2/s for treatment in an acetone-based electrolyte for 1 min. The obtained values were comparable with the calculation results for the thickness of the pearlite layer after anodic plasma electrolytic carburising as well as data of measurements of the distribution of carbon concentration in the carburised layer after cathodic saturation. The influence of the oxide layer inhibiting the diffusion of carbon and the possibility of controlling its thickness by varying the concentration of ammonium chloride, which provides anodic dissolution of steel, were confirmed. It has been established that the published values of the coefficients of carbon diffusion during plasma electrolytic carburising relate to various structures whose characteristics and properties depend on the composition of the working electrolytes and processing conditions.